Evaluation of Temperature and Surface Humidity Variability of the Troposphere Using Radiosonde Observations - Awalia 'Ulyan Najah; Nenni Mona Aruan; Siswanto Siswanto (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2026)
This study aims to evaluate the variability of surface atmospheric temperature and humidity and the implications for atmospheric stability based on observation data at the Juanda-Sidoarjo Class 1 Meteorological Station in February 2026. The method used is a quantitative approach with descriptive and evaluative analysis of temperature and humidity data at two observation times. So the results show that the temperature during the day has a greater variation of around 24.6°C to 30.0°C while the relative humidity is around 67% to 97%. Likewise, at night it has a larger variation, around 24.3°C to 26.3°C, while the relative humidity is higher, around 81% to 96%. This analysis shows an inverse relationship between temperature and humidity, where temperature increase is followed by a decrease in relative humidity. The atmospheric dynamics side of daytime conditions produces labile atmospheric conditions due to intense surface heating, while for nighttime it shows stable atmospheric conditions due to surface cooling. So that temperature and humidity variability play an important role in controlling atmospheric stability and weather dynamics in tropical regions.